PENGGUNAAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SIFAT-SIFAT BANGUN DATAR DI SEKOLAH DASAR - Syafri Ahmad (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
This research was conducted as the teacher had not yet used group dynamics in teaching the characteristics of shapes topics. This had made the learning process became teacher-centered and the students’ learning achievement got low. The purpose of this research was to describe the improvement of the students’ learning achievement on the characteristics of shapes topics by using jigsaw cooperative learning model. This reseach was conducted at SDN 03 Pelangai Gadang. The subject of the research was the teacher and the fifth grade students. The result of the research indicated that there was an improvement on the plan, the implementation of the plan and the students’ learning achievement. This result had indicated that the use of jigsaw cooperative learning model could improve the students’ learning achievement on the characteristics of shapes topic in the fifth grade of SDN 03 Pelangai Gadang.